Hadronic matter under an external magnetic field: In-medium modification of the pion mass - Aguirre, Ricardo Miguel (2017)
The covariant propagator of a fermion with intrinsic magnetic moment interacting with a uniform external magnetic field is presented for finite temperature and baryonic density. The case of a scalar boson is also considered. The final expressions are given in terms of a four-dimensional momentum representation. These results, which take account of the full effect of the magnetic field, are used to evaluate the modification of the pion mass at zero temperature as a function of the density and the magnetic intensity. For this purpose a self-consistent calculation, including one- and two-pion vertices, is employed.